An evaluation study of the trace element (Chromium) and it’s severity in progression of diabetes mellitus type 1 and 2 - Jadoo, Mohammad Odeh.; Thuwaini, Mahdi. M.; Khalaf, Qasim H. (Edelweiss Applied Science and Technology, 2025)
The physiological functions of the human body depend on micronutrients called trace elements, which are essential in a number of metabolic pathways. Consequently, these deficiencies are associated with a number of chronic illnesses, such as diabetes mellitus. This study aimed to evaluate the relationship and severity of chromium in type 1 and type 2 diabetes, and to assess the correlations of chromium with some parameters in diabetes mellitus. There were 100 DM patients and 100 healthy controls in the current study. T1D affects people between the ages of 10 and 23 years, while T2D affects people between the ages of 40 and 70 years. The age of the controls and the patients was the same. The serum concentration of trace elements (chromium) was determined by a specific spectrophotometry flameless atomic absorption method utilizing an atomic absorption spectrophotometer. Chromium was determined at a wavelength of 357.9 nm, applying a slit width of 0.7 nm and a lamp current of 10 mA. To measure insulin and C-peptide, the Cobas Roche E411 was used, and to measure GAD antibodies, Magliume was utilized. Observations revealed that the mean concentration of Cr (0.6205 ± 0.40119) vs. (0.6775 ± 0.20316) (μg/L) showed a non-significant p-value (0.387) in patients with type 1 diabetes when compared to the control group. In contrast, the mean level of concentration Cr (0.2614 ± 0.14735) vs. (0.6667 ± 0.20141) (μg/L) significantly decreased (p-value = 0.0001) in patients with type 2 diabetes when compared to the healthy group. The findings of other parameters significantly decreased in patients with type 1 diabetes when compared to the healthy group (HOMA-IR, insulin, C-P) (P = 0.000, P = 0.000, P = 0.000). Meanwhile, GAD showed a significant increase in patients with type 1 diabetes when compared to the control group (p = 0.000). The results of other parameters in type 2 diabetes (HOMA-IR, insulin, C-P, GAD) showed a significant increase in patients with type 2 diabetes when compared to the control group (p = 0.0001, p = 0.0001, p = 0.0001, and P-value = 0.038). The current findings suggest that serum concentrations of the vital trace element chromium are connected to the existence of diabetes mellitus type 2 but not type 1. These findings contribute to the growing body of data showing the utility of chromium for proper glucose metabolism, creation, storage, and release of insulin, and help in normal insulin function. There are no correlations between chromium and other parameters in diabetes type 1 and type 2.